Analisis Literasi Informasi Reporter di Komunitas Pena Lingkar Toba Kelas Puisi - Barus, Putri Charolina; Harahap, Nursapia (Universitas Sebelas Maret Library, 2023)
The author's Information Literacy Analysis in creating his study work is still small in various communities. This qualitative study aims to obtain the author's information literacy ability in creating works in the Toba Circle Pen community or abbreviated as PELITO. This study involved 6 authors who were positioned as research subjects. Data on the author's information literacy ability are collectedusing a recording device, which is then recorded in word. The collected data is analyzed using thematic analysis. The results of this study inform that the information literacy ability of each writer in making a work in the category is quite good. Furthermore, the author's way of searching for more detailed information will easily create a work, rather than one that only relies on imagination and reads less. Following up on these findings, literation skills in various communities must be optimized through reading a lot, increasing learning resources, and learning to browse information through the internetor observation.